A study of the electrical properties of complex resistor network based on NW model. (March 2015) - Chang, Yunfeng; Li, Yunting; Yang, Liu; Guo, Lu; Liu, Gaochao
Abstract: The power and resistance of two-port complex resistor network based on NW small world network model are studied in this paper. Mainly, we study the dependence of the network power and resistance on the degree of port vertices, the connection probability and the shortest distance. Qualitative analysis and a simplified formula for network resistance are given out. Finally, we define a branching parameter and give out its physical meaning in the analysis of complex resistor network.